A Novel Observer Design for Sensorless Sampled Output Measurement: Application of Variable Speed Doubly Fed Induction Generator. Issue 13 (2016) - Al Tahir, A.A.R.; Lajouad, R.; Chaoui, F.Z.; Tami, Ramdane; Ahmed-Ali, T.; Giri, F.
Abstract: This paper presents a novel exponentially convergent nonlinear observer design for variable speed doubly fed induction generators (DFIG). The main feature of the proposed observer lies in the use of sampled-data without necessitating mechanical sensors, making the observer more reliable. A main component of the observer is an inter-sampled predictor of the output current vector. The observer exponential convergence is established and analyzed using Lyapunov stability technique and the small gain theorem. The proposed observer combines the advantage of a high-gain structure in terms of convergence speed and the continuity of the estimated state trajectory. One difficulty of the present observer design problem is that the electromagnetic torque is not related to the output by an injective map. The simulation results in variable speed DFIG operation are provided to confirm the theoretical results.